Convalescent pigs are protected completely against infection with a homologous Actinobacillus pleuropneumoniae strain but incompletely against a heterologous-serotype strain. - Cruijsen, T (1995)
To study whether Actinobacillus pleuropneumoniae induces a species-specific immunity, we infected pigs in the left lung with serotype 3 or 9 and after 3 weeks we infected their right lungs with serotype 9. Convalescent pigs were protected against homologous strain reinfection, but after heterologous strain reinfection the degree of protection varied. Neutralizing antibodies were not essential for protection.